2012
DOI: 10.1177/0961203311434938
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies associated with RNA are more enriched than anti-dsDNA antibodies in circulating immune complexes in SLE

Abstract: To what extent different autoantibodies accumulate in systemic lupus erythematosus (SLE) immune complexes (ICs), and whether such accumulation is associated with disease activity has been investigated. ICs were isolated from SLE sera by both polyethylene glycol (PEG) precipitation and C1q-binding. Autoantibody specificities were determined using a lineblot assay quantified by densitometry. To compare the relative levels of autoantibodies, levels were normalized to the total levels of IgG measured by ELISA in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…This is supported by clinical data that shows a preferentially higher TLR-7 expression in SLE patients with an anti-RNA-associated antibody profile (47). Additionally, it has recently been shown that RNAassociated antibodies are more prone to form circulating ICs compared to antibodies to dsDNA (48). U1 RNA, which forms the U1 snRNP complex together with Sm and RNP proteins (49), is elevated in the circulation of SLE patients and correlates with disease activity (50).…”
Section: Discussionmentioning
confidence: 78%
“…This is supported by clinical data that shows a preferentially higher TLR-7 expression in SLE patients with an anti-RNA-associated antibody profile (47). Additionally, it has recently been shown that RNAassociated antibodies are more prone to form circulating ICs compared to antibodies to dsDNA (48). U1 RNA, which forms the U1 snRNP complex together with Sm and RNP proteins (49), is elevated in the circulation of SLE patients and correlates with disease activity (50).…”
Section: Discussionmentioning
confidence: 78%
“…Since endosomal TLRs have a much more controlled mechanism of antigen exposure and are not free to sample the environment in an unregulated manner, this may explain why positive agonist-induced regulation of receptor expression may only exist in TLRs localized to endosomes. Endosome-associated TLRs exclusively bind to nucleic acids and SLE patients often secrete high levels of anti-nuclear antibodies (ANA), which results in circulating immune complexes consisting of antibodies to self nucleic acids [53]. Our data suggest that processing of these complexes could cause a ligand-induced up-regulation of receptor expression, which would be more robust in an environment containing estrogen and therefore contribute to autoimmune development.…”
Section: Discussionmentioning
confidence: 98%
“…Soluble immune complexes in lupus sera have been analyzed by precipitation in polyethylene glycol (PEG) or by their binding to C1q (Skinner and Maddison, 1990; Ahlin et al, 2012). The two methods are not completely identical, as lupus patients also produce autoantibodies to the collagen like domain of C1q that bind independent of immune complexes (Uwatoko and Mannik, 1988; Mannik and Wener, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The two methods are not completely identical, as lupus patients also produce autoantibodies to the collagen like domain of C1q that bind independent of immune complexes (Uwatoko and Mannik, 1988; Mannik and Wener, 1997). Detailed analysis of PEG precipitated immune complexes from lupus patients suggests that the circulating complexes are enriched in antibodies binding RNA but not anti-double stranded DNA (Ahlin et al, 2012). This is consistent with the frequent finding of antibodies to Ro52 and RNP in the SLE15 purified IgG from both lupus and control sera.…”
Section: Discussionmentioning
confidence: 99%